Project LifeSkills - a randomized controlled efficacy trial of a culturally tailored, empowerment-based, and group-delivered HIV prevention intervention for young transgender women: study protocol - Lisa M. Kuhns; Matthew J. Mimiaga; Sari L. Reisner; Katie Biello; Robert Garofalo (BMC, 2017)
Abstract Background Transgender women in the U.S. have an alarmingly high incidence rate of HIV infection; condomless anal and vaginal sex is the primary risk behavior driving transmission. Young transgender women are the subpopulation at the highest risk for HIV. Despite this, there are no published randomized controlled efficacy trials testing interventions to reduce sexual risk for HIV among this group. This paper describes the design of a group-based intervention trial to reduce sexual risk for HIV acquisition and transmission in young transgender women. Methods This study, funded by the National Institutes of Health, is a randomized controlled trial of a culturally-specific, empowerment-based, and group-delivered six-session HIV prevention intervention, Project LifeSkills, among sexually active young transgender women, ages 16-29 years in Boston and Chicago. Participants are randomized (2:2:1) to either the LifeSkills intervention, standard of care only, or a diet and nutrition time- and attention-matched control. At enrollment, all participants receive standardized HIV pre- and post-test counseling and screening for HIV and urogenital gonorrhea and chlamydia infections. The primary outcome is difference in the rate of change in the number of self-reported condomless anal or vaginal sex acts during the prior 4-months, assessed at baseline, 4-, 8-, and 12-month follow-up visits. Discussion Behavioral interventions to reduce sexual risk for HIV acquisition and transmission are sorely needed for young transgender women. This study will provide evidence to determine feasibility and efficacy in one of the first rigorously designed trials for this population. Trial registration ClinicalTrials.gov number, NCT01575938 , registered March 29, 2012.